The correlation between sperm DNA methylation and DNA damage: a comparison of comet and TUNEL - Zimmerman, Hailey; Jenkins, Tim (Frontiers in Reproductive Health, 2025)
ObjectiveTo evaluate the relationship between sperm DNA methylation and DNA damage as determined by the comet or TUNEL assays.DesignRetrospective research study.SettingUniversity-based andrology and in vitro fertilization (IVF) laboratory.Patient(s)Data came from 1,470 male partners (ages 18 and older) recruited from heterosexual couples (ages 18–45 years) seeking fertility treatments. These data were analyzed retrospectively from the Folic Acid and Zinc Supplementation Trial (FAZST) study.Main outcome measure(s)Comet and TUNEL measures and associations with DNA methylation patterns.Result(s)Comet and TUNEL values were correlated with one another across all samples (R2 = 0.34, P < 0.001); however, when assessing the highest and lowest scores reported from each assay, there was little overlap between patients. This suggests that Comet and TUNEL are identifying key differences that may be meaningful and correlated with other sperm metrics. We compared both comet and TUNEL to methylation array data using a sliding window analysis, which identified far more significantly differentially methylated sites as a function of comet than TUNEL (3,387 vs. 23). Interestingly, sites associated with comet were associated with biological pathways related to DNA methylation involved in germline development, as determined by a GO term analysis. The TUNEL assay, by comparison, produced no relevant biological pathways.Conclusion(s)Because the comet and TUNEL assays are both used to indicate levels of DNA damage, and outputs of both are correlated to each other, it would seem to follow that both are equally predictive of deviations in DNA methylation patterns. The findings of this study suggest that this is not the case. The comet assay shows a significantly higher association with DNA methylation disruption, and we therefore believe it to be a better indicator of sperm epigenetic health.